Optimalisasi Standart Operasional Prosedur (SOP) Alur Retur Produk Guna Meningkatkan Efisiensi Operasional pada PT Aaron Innovation - Amalia Putri Febrianti; Sugeng Purwanto (Pusat Riset dan Inovasi Nasional, 2024)
PT Aaron Innovation is a company that focuses on marketing yummys mother and child products, such as breast milk, maternity food, and baby skincare. With the wider reach of consumers through the TikTok platform, the company faces the challenge of increasing product return rates. This study aims to optimize the product return process at PT Aaron Innovation by identifying and implementing strategies that can increase operational efficiency, reduce costs, speed up and improve the accuracy of return handling, and increase customer satisfaction. This study uses a descriptive qualitative approach with a survey method, collecting data through direct observation and interviews with sources. The results showed that the current returns system is not optimal, with ineffective SOPs and a lack of special areas for returns handling, causing delays and irregularities in handling returned products.